2007
DOI: 10.1007/s11259-007-9024-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enrofloxacin on canine tendon cells and chondrocytes proliferation in vitro

Abstract: Enrofloxacin, a fluoroquinolone antibiotic has been used widely in humans and domestic animals, including dogs, because of its broad-spectrum activity and relative safety. The side effects of fluoroquinolone, induced tendinopathy, tendonitis, spontaneous tendon rupture and cartilage damage, remain incompletely understood. In the present study, we investigated the in vitro effects of enrofloxacin on cell proliferation and induction of apoptosis in canine Achilles tendon cells and chondrocytes. Cell growth and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…The safety of Enro has been demonstrated through the high ability of human foreskin fibroblasts to defend themselves against protozoan parasite infection, without cell toxicity (Barbosa et al ., ). However, the effects of Enro on cell proliferation, DNA fragmentation, and apoptosis induction have been reported in canine tendon cells and chondrocytes (Lim et al ., ) and in avian and equine tenocytes (Yoon et al ., ,b). The mechanisms of FQ‐induced cell apoptosis remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of Enro has been demonstrated through the high ability of human foreskin fibroblasts to defend themselves against protozoan parasite infection, without cell toxicity (Barbosa et al ., ). However, the effects of Enro on cell proliferation, DNA fragmentation, and apoptosis induction have been reported in canine tendon cells and chondrocytes (Lim et al ., ) and in avian and equine tenocytes (Yoon et al ., ,b). The mechanisms of FQ‐induced cell apoptosis remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the cytotoxic and apoptosis-inducing effects of FQ antibiotics on tendon cells, chondrocytes, and a variety of human cancer cell lines [8], [25][29]. However, previous studies used a wide range of concentrations, and multiple mechanisms of action have been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…While post-operative limb-spare infections are quite common in the dog, multiple studies have found such infections to be associated with improved survival when compared with similarly treated dogs without infection [3][5]. One such study reported that 24 out of 32 dogs experiencing post-operative allograft infections were treated with fluoroquinolone antibiotics [3], a class of drugs known to have independent activity against several tissue and cancer cell lines in vitro and in vivo [6][8]. Fluoroquinolones (FQs), such as ciprofloxacin (CPFX) and enrofloxacin (ENFX), target topoisomerase enzymes and in this way share a similar mechanism to traditional anti-neoplastic agents such as doxorubicin, irinotecan, and etoposide [6], [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Myxomatous degeneration can be observed in ciprofloxacin and pefloxacin treated rats (Olcay et al 2011). Following exposure to pefloxacin, ofloxacin (Kato et al 1995) or enrofloxacin (Lim et al 2008), nuclei of tenocytes became pyknotic and fragmented. Such degenerative ultrastructural changes observed in the Achilles tendon samples from rats treated with gemifloxacin, ofloxacin or ciprofloxa- The quinolone core is shown at top.…”
Section: Ultrastructural Degenerative Changesmentioning
confidence: 99%